Pelaksanaan Kegiatan Bersama sebagai Suatu Upaya Peningkatan Hubungan Baik dengan Masyarakat Kelurahan Wirolegi - Putri Iswari Dewi; Siti Nurul Laili; Rahman Fauzi; Novarian Sofoi Caldera; Dita Atasa (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Collaborative Real Lecture Work (KKN) #2 in the Wirolegi sub-district, Jember Regency is a real form of community empowerment. KKN collaboratively brings together students from various universities and study programs to find solutions for sub-districts. In its implementation, Collaborative KKN #2 students established positive interactions with various ages and used survey and observation-based methods. The main goal is to increase student empathy, interest and participation in solving local problems. Additional activities such as activities with village heads, gymnastics, competitions and tree planting in elementary schools are also carried out to strengthen ties and have a positive impact on the community. The formation of an inter-university group in Collaborative KKN #2 shows the success of combining various thoughts and skills to solve problems. Active communication between students, subdistricts and educational institutions is very important to maintain long-term relationships and ensure sustainable development in the Wirolegi subdistrict.